1990
DOI: 10.1093/jn/120.5.459
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of Vegetable Fiber in the Intestinal Tract of Rats and Effects on Fecal Bulking and Bile Acid Excretion

Abstract: The fermentative breakdown and fecal bulking capacity of dietary fiber from various vegetables (carrots, rutabagas, peas, green beans and Brussels sprouts) were evaluated in balance experiments in rats. The excretion of bile acids, protein and fat was also studied. The addition of blanched vegetables providing 10 g of fiber/100 g of diet caused a two-(rutabagas) to threefold (carrots) increase in fecal dry weight compared to that with a basal fiber-free diet. With green beans and Brussels sprouts, only about 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
21
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 22 publications
9
21
1
Order By: Relevance
“…An increase of 105% and 86% in fresh and dry faecal weights respectively was noted for fibre-fed rats when compared to the control group. These results are comparable to those obtained in similar studies carried out utilizing high-fibre containing diets (Nyman & Asp, 1982;Nyman et al, 1990;Bravo et al, 1992).…”
Section: Pharmacological Investigationsupporting
confidence: 89%
See 2 more Smart Citations
“…An increase of 105% and 86% in fresh and dry faecal weights respectively was noted for fibre-fed rats when compared to the control group. These results are comparable to those obtained in similar studies carried out utilizing high-fibre containing diets (Nyman & Asp, 1982;Nyman et al, 1990;Bravo et al, 1992).…”
Section: Pharmacological Investigationsupporting
confidence: 89%
“…Results attained in the pharmacological investigation are expected to be reconfirmed if tested in human subjects since a correlation has been established between this rat model and humans (Nyman et al, 1990). …”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Thus, earlier studies in man showed an increased faecal bulk when carrots (200È688 g) (Robertson et al 1979a ;Wisker et al 1994) or carrot Ðbre (20 g) (Cummings et al 1978) were added to the diet for 3 weeks. Similar e †ects have been demonstrated in rats (Nyman et al 1990(Nyman et al , 1991. However, the e †ect of processing is less clear.…”
Section: Introductionsupporting
confidence: 79%
“…Structural tissues located in the rind are characterized by fibres and xylem vessels with secondarily thickened cell walls embedded in parenchymatous ground tissue. As they contain a higher proportion of cellulose and lignin than thin-walled parenchyma, they may be more resistant to hind gut fermentation, so they may have a valuable role in conferring the wide range of benefits to large bowel health that are thought be derived from bulk in the distal colon [11,25].…”
Section: Introductionmentioning
confidence: 99%